2016
DOI: 10.17159/2078-516x/2016/v28i2a163
|View full text |Cite
|
Sign up to set email alerts
|

Physiological responses of batsmen during a simulated One Day International century

Abstract: Background: There is a limited amount of literature on the physiological cost of batting. Of the studies that have been completed, most have used protocols that are of short duration and high intensity, and it has been questioned whether this represents actual game play. Furthermore, it is difficult to study sports such as cricket due to the intermittent nature of the game. Objective: To determine the physiological responses of batsmen during a simulated One Day International century. Methods: Seventeen male b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 11 publications
0
4
0
Order By: Relevance
“…The differences in laboratory and fieldbased testing also need to be considered when disseminating these results; more variables can be controlled for in the laboratory, but this may impact the ecological validity. For example, it needs to be recognised that factors such as player and competition dynamics, (e.g., scoreboard pressure and importance of match) were not considered in this investigation which may have impacted results [24]. This is an area that could be looked at in more detail in future research.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The differences in laboratory and fieldbased testing also need to be considered when disseminating these results; more variables can be controlled for in the laboratory, but this may impact the ecological validity. For example, it needs to be recognised that factors such as player and competition dynamics, (e.g., scoreboard pressure and importance of match) were not considered in this investigation which may have impacted results [24]. This is an area that could be looked at in more detail in future research.…”
Section: Resultsmentioning
confidence: 99%
“…These findings are also accurate when compared to real-time matchplay, where heart rate responses of 139-154 beats/min, and 149-167 beats/min have been shown for batters in ODIs and T20 matches respectively [16,20]. Furthermore, simulated ODI century protocols have also been undertaken in a laboratory setting (focusing on longer duration and lower intensities); these investigations identified heart rate responses between 130 and 144 beats/min and an oxygen consumption of 36.70 mL/kg/min [11,24].…”
Section: Introductionmentioning
confidence: 99%
“…thus, there is a need to implement repeat sprint ability training (such as 25-m shuttles) to focus on eccentric loading of the lower limbs and thus avoid injuries. Furthermore, studies on batsmen have shown a decrease in eccentric peak torque of the knee flexors and extensors when running between the wickets (during high intensity running in a 7-over period), potentially increasing the risk of hamstring strains [2], thus further proving the importance of eccentric work through repeat sprint training.…”
Section: Discussionmentioning
confidence: 99%
“…the game of cricket is played in over 100 countries worldwide and is constantly growing in popularity [1]. the first form of the game, the 5-day test match, has evolved into a 1-day game and more recently into the 20-over format [1,2] and the game is a lot more physically demanding than it used to be [3]. Furthermore, with the introduction of different match formats, players are subjected to longer seasons and increased workloads.…”
Section: Introductionmentioning
confidence: 99%